A Single Center Anesthesia Experience in Children Posted for Cleft Lip and Palate Repair: A Retrospective Analysis from a Post-Anesthesia Care Unit - Taşdoğan, Ali Muhittin; Tarıkçı Kılıç, Ebru (European Journal of Therapeutics, 2023)
Objective: Cleft lip and palate (CLP) is one of the most commonly seen craniofacial abnormalities in children. Anesthesia management for these surgeries is challenging due to the emergence of airway problems and perioperative complications. In this study, we aimed to evaluate airway difficulties and perioperative anesthetic complications in children suffering from CLP. Methods: After obtaining approval from the institutional review board, this retrospective study was conducted on 29 children that underwent CLP repair from January 2014 to December 2016 at a single center. Demographic parameters, patients with CLP, patients having micrognathia, associated syndromes, associated congenital abnormalities, difficult mask ventilation, difficult intubation, duration of anesthesia, number of intubated patients to be transferred to the post-anesthesia care unit (PACU), airway-associated complications, and intraoperative and postoperative complications were recorded. Results: Data from a total of 29 patients with cleft palate were included. Out of the 29 patients, 15 patients had a cleft lip, 17 patients had micrognathia, and 10 patients had both cleft lip and micrognathia. Three patients had difficult mask ventilation, while seven had difficult intubation. Intubation failure was seen in three patients in whom a fiber optic laryngoscope was successfully utilized. Airway-associated complications were seen in six patients. Only three patients had postoperative complications. There were no mortalities. Conclusion: CLP deformities in children with associated abnormalities are predisposed to difficult airway-associated and postoperative complications. Specialized perioperative care is necessary.